The Beaver Hall Group and its Place in the Montreal Art Milieu and the Nationalist Network - Avon, Susan (Université Concordia, 1994)
Keywords: Clubs; Nationalisme

Un peintre allemand à Montréal - Béland, Mario (Cap-aux-Diamants, 1994)
Keywords: Allemands; Peinture

L'abstraction à Montréal 1950-1970 - Blais, Simon (Parcours, l'informateur des arts, 1994)
Notice DG
Keywords: Expositions; Peinture

Étude de l'action, de la pensée esthétique et de la démarche plastique de Fernand Leduc de 1953-1959 - Dupont, Louise (Université Laval, 1994)
Keywords: Automatistes; Peinture

Marc-Aurèle Fortin: à l'ombre des grands ormes - Gagnon, Daniel (XYZ, 1994)
Keywords: Peinture

JULIEN, HENRI - Guilbault, Nicole (Dictionnaire biographique du Canada, 1994)

Le Devoir et l'Art au vingtième siècle au Québec - Lacroix, Laurier (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

CAPELLO, LUIGI GIOVANNI VITALE - Lacroix, Laurier; Shtychno, Alexandra (Dictionnaire biographique du Canada, 1994)

SANDHAM, HENRY - Landry, Pierre B. (Dictionnaire biographique du Canada, 1994)

L'influence du Centre copie-art de 1982 à 1992 pour la reconnaissance et la légitimation de la copigraphie à Montréal - Mongeau, Alain (Université du Québec à Montréal, 1994)

Un état de la diffusion des arts visuels à Montréal. Les années cinquante: lieux et chronologie Première partie: 1950-1955 - Sicotte, Hélène (Annales d'histoire de l'art canadien / Journal of Canadian Art History, 1994)
Keywords: Expositions

The Relationship between Montreal Artist-Run Centres and Art Museums - Spicer, Valérie (Université de Montréal, 1994)
Keywords: Musées

Sidney Carter (1880-1956) and the Politics of Pictorialism - Strong, David Calvin (Université Concordia, 1994)
Keywords: Photographie

Représentation de l'espace urbain et laïcisation de la pratique - Trépanier, Esther (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Les photographies composites de William Notman / The composite photographs of William Notman - Triggs, Stanley (Musée McCord d'histoire canadienne, 1994)
Keywords: Notman, William; Photographie